Cognitive Mastery in Sports: Exploring Cognitive Psychology's Influence - Ghasemzadeh, Azizreza; Saadat, Maryam (Health Nexus, 2023)
This article delves into the pivotal role of cognitive psychology in sports, illuminating its profound impact on athletes' performance. Over a comprehensive survey of literature spanning the past decade, this review synthesizes key developments and applications of cognitive psychology in the athletic domain. Utilizing databases such as PubMed, PsycINFO, Google Scholar, and SportDiscus, the study employs a meticulous selection process, focusing on peer-reviewed articles that significantly contribute to the understanding of cognitive training, assessment, and rehabilitation in sports. The review explores diverse facets of cognitive psychology in sports, including the theoretical underpinnings of cognitive functions, innovative cognitive training interventions, and the crucial role of mental processes in injury recovery. It presents an analysis of the effectiveness of various cognitive strategies in enhancing athletic performance and resilience. Additionally, it addresses the challenges and potential future directions of cognitive psychology applications in sports. This article aims to bridge the gap between cognitive psychological theory and practical sports applications, offering insights for athletes, coaches, and sports psychologists. By highlighting the symbiotic relationship between the mind and athletic prowess, "The Mind Game" underscores the transformative potential of cognitive psychology in elevating sports performance to new heights.